Eksplorasi Karakter Empati Siswa SMA dalam Interaksi Sosial di Lingkungan Sekolah - Nathasya, Firdaus Christina; Winingsih, Evi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to understand the development of empathy character among senior high school students in social interactions within the school environment and to examine how empathy is formed and practiced in daily life. The research employed a qualitative method with a phenomenological approach to explore students’ lived experiences related to empathy. The research subjects consisted of four twelfth-grade students at a public senior high school in Surabaya, selected through purposive sampling. Data were collected through observation and in-depth interviews, and analyzed using the Miles and Huberman interactive model, which includes data collection, data reduction, data display, and conclusion drawing. The findings indicate that students’ empathy character develops through several processes, including awareness of peers’ conditions, the emergence of socially caring actions, and an understanding of empathy as an essential value in maintaining friendships. Empathy is manifested in concrete behaviors such as listening to peers, helping friends, and providing emotional support. However, this character has not yet developed optimally due to the influence of both internal and external factors. These findings suggest that empathy is a social character that does not emerge instantly but is formed through ongoing social interaction experiences. Therefore, strengthening empathy requires planned efforts in the educational context, particularly through character education and school culture, to foster social sensitivity and care, ultimately creating a more positive school environment.